The implementation of tree preservation order in urban environment: public and local authority perception - Ibrahim, Putri Haryati; Zahrull Pauzi, Hani Farina; Mohd Masri, Nur Nazifah (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
Trees are natural assets that play a vital role in the environment and living things on earth. Every tree has its own values, importance and benefits that can make a huge impact, especially in terms of enhancing the urban environment. Thus, the Tree Preservation Order (TPO) has been introduced all over the world, including Malaysia, to protect the trees. Although there are numerous studies about the importance of trees in urban areas, there are still not many studies on the TPO in Malaysia. The implementation of TPO in Malaysia is still not sufficient because of the awareness and challenges in implementing the order. This study analyses the perceptions of the public and local authorities in implementing the TPO in the urban environment. The study managed to get fifty (50) respondents from the questionnaire survey conducted, and interview four representatives from the Department of Landscape and Recreation Development and Department of Planning of Kuala Lumpur City Hall (KLCH). The officers were interviewed in order to study the perception of the local authority on implementing the TPO in urban environment. Based on the result obtained, the study found out that the public has awareness, knowledge and proper understanding of the implementation of TPO. However, according to the local authority, the public’s awareness and knowledge of TPO is still lacking. The local authority faces several issues and challenges in implementing the TPO because of the lack of the awareness of TPO on the part of the public. Hence, public awareness and knowledge can also help the local authority in the implementation of TPO in the urban environment.